Pengaruh Kualitas Pelayanan Terhadap Kepuasan Masyarakat Di Kabupaten Gowa - Fatika Sari, Nur Aisyah; Parawu, Hafiz Elfiansyah; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
This study aims to determine the effect of service quality on public satisfaction at the Gowa Regency Public Service Mall. The research method used is quantitative with data collection techniques through questionnaires, observation, and documentation. A sample of 100 respondents was selected using the Accidental Sampling technique. Data collection techniques in this study: Descriptive Statistics, Validity Test, Reliability Test, Simple Regression Analysis, Hypothesis Test. The results of the study indicate that service quality consisting of tangibles, reliability, responsiveness, assurance, and empathy dimensions has a positive and significant effect on public satisfaction. This is evidenced by a partial test which shows a significant value of 0.000 <0.05, it is known that the coefficient of determination R square has a value of 0.513 or 51.3%. Thus, improving service quality can increase public satisfaction with the services provided at the Gowa Regency Public Service Mall.